UM ESTUDO EXPERIMENTAL SOBRE A FILTRAÇÃO ADICIONAL DO FEIXE DE RAIOS X COM NANOMATERIAL - Ibaldo, Juliano Martinuzzi (2023)
Conventional radiological equipment employed in medicine uses radiation beam attenuation filters to eliminate, or at least reduce, low energy photons. The filters used are generally made of aluminum (Al) with different thicknesses, usually from 1 to 3 mm. The aluminum filter is an essential accessory for the quality of the beam used in medical radiology. The low energy photons that are part of the radiation beam emitted by the X ray tube do not contribute to the formation of the radiological image. In fact, they only increase the dose received by the patient since the low energy photons are absorbed by the superficial tissues, and do not reach the image receptor. Current standards require that all equipment used in medical radiology should have minimum filtration that varies according to specific area. In this study, we added an aluminum filter coated with a biopolimer nanocomposite to the x-ray tube on its external part. For this experiment, we used a nanomaterial formed by aluminum nitrate and sodium hydroxide forming an aluminum hydroxide solution that was structured with chitosan. The nanocomposites were characterized through scanning electron microscopy and X-ray Energy Dispersive Spectroscopy. The aluminum filter coated with the nanocomposite was exposed to x-radiation in conventional radiology equipment using variable voltage exposure factors and the beam attenuation was measured using a radiation detector for different electrical factors selected on the control panel of radiographic equipment. The voltage values were increased in constants of 10 , while the values of electric current by the exposure time (milliamperage per second - mAs) remained fixed. The obtained results showed that the values of the semi reducing layer reduced when we used low energies and remained unchanged when high energies were selected on the control panel. The reduction observed for the semi reducing layer is extremely relevant since it implies an increase in the attenuation of the radiation bean. In addition, from the X-ray images which were analyzed using a digital image visualization software, it was possible to observe that the addition of nanocomposites to the aluminum filter reduces the noise in the images without changing their quality. The noise value found when using the nanocomposites decreased from 15 to 20% in relation to the noise value found in the image without additional filtration. Moreover, we observed an increase in the signal-to-noise ratio, which means an improvement in image quality when we used low energies. These findings suggest that these nanocomposites can be used in radiation beam quality control tests and with the possibility of application in the radiological area.